Regenerative Therapy Prevents Heart Failure Progression in Dyssynchronous Nonischemic Narrow QRS Cardiomyopathy. Issue 5 (May 2015) - Yamada, Satsuki; Arrell, D. Kent; Martinez‐Fernandez, Almudena; Behfar, Atta; Kane, Garvan C.; Perez‐Terzic, Carmen M.; Crespo‐Diaz, Ruben J.; McDonald, Robert J.; Wyles, Saranya P.; Zlatkovic‐Lindor, Jelena; Nelson, Timothy J.; Terzic, Andre
Abstract : Background: Cardiac resynchronization therapy using bi‐ventricular pacing is proven effective in the management of heart failure (HF) with a wide QRS‐complex. In the absence of QRS prolongation, however, device‐based resynchronization is reported unsuitable. As an alternative, the present study tests a regenerative cell‐based approach in the setting of narrow QRS‐complex HF. Methods and Results: Progressive cardiac dyssynchrony was provoked in a chronic transgenic model of stress‐triggered dilated cardiomyopathy. In contrast to rampant end‐stage disease afflicting untreated cohorts, stem cell intervention early in disease, characterized by mechanical dyssynchrony and a narrow QRS‐complex, aborted progressive dyssynchronous HF and prevented QRS widening. Stem cell‐treated hearts acquired coordinated ventricular contraction and relaxation supporting systolic and diastolic performance. Rescue of contractile dynamics was underpinned by a halted left ventricular dilatation, limited hypertrophy, and reduced fibrosis. Reverse remodeling reflected a restored cardiomyopathic proteome, enforced at systems level through correction of the pathological molecular landscape and nullified adverse cardiac outcomes. Cell therapy of a dyssynchrony‐prone cardiomyopathic cohort translated prospectively into improved exercise capacity and prolonged survivorship. Conclusions: In narrow QRS HF, a regenerative approach demonstrated functional and structural benefit, introducing the prospect of device‐autonomous resynchronization therapy for refractory disease.